Preparação de pigmentos cerâmicos à base de cinza da casca de arroz impregnados com íons ferro e cromo - Dantas, Gerbeson Carlos Batista (2021)
Rice husk is an agro-industrial residue that, due to its large volume and inadequate destination, can cause contamination of environmental systems, in addition to posing risks to human health. The ashes from the burning of this residue have already been used as raw material in the synthesis of silica catalysts, adsorption, in mortars, concretes and soil-lime bricks. However, with the increasing increase in rice production in Brazil, it becomes necessary to develop alternatives for the application of this residue. In this context, this work aims to study the technical feasibility of using rice husk ash as a ceramic pigment from the impregnation of Fe3+ and Cr3+ chromophores, evaluating its stability and color properties. Initially, the rice ash was sieved through a 200 mesh (0.0074mm). Then, 15% of Fe3+ and Cr3+ ions were incorporated into the material through the wet impregnation method, dried in an oven and heat treated at temperatures of 800 °C or 1000 °C. Then, they were characterized by X-ray fluorescence, Xray diffraction, scanning electron microscopy with EDS mapping and colorimetry. The pigments were mixed with glossy clear glazes in proportions of 3% by weight. These mixtures were then used to coat the substrates. The coated substrates were sintered at temperatures 1050, 1100 or 1150 °C to determine thermal stability. The results showed that the bark ash had high silica content (> 70%), with high iron oxide content and presence of chromium oxide in the samples modified by Fe3+ and Cr3+ ions, respectively. X-ray diffractograms revealed a predominant presence of amorphous silica, with partial crystallization when heat-treated. The mapping detected, in addition to the increase in Fe3+ and Cr3+ concentrations in the modified samples, a homogeneous distribution of chromophores in the pigments. Pigments incorporated with Fe3+ and Cr3+ were colored red and green, respectively. However, after ceramic coating, the glazes incorporated with the pigment modified by Fe3+ showed a shift towards the yellow region. No significant change was observed in the glazes hue with the variation of the sintering temperature, except at 1050 °C, which did not glaze. Therefore, based on the results, rice husk ash incorporated with Fe3+ or Cr3+ by the wet impregnation method presented properties compatible with those of pigments widely used in the ceramic industry